The Study of Relationship of Soil Physics Health and Micro-Climate Characteristics on Paddy Fields - Sumani, Sumani; Widhiyastuti, Alfia Nisa; Mujiyo, Mujiyo; Herdiansyah, Ganjar; Maro’ah, Siti (Journal of Applied Agricultural Science and Technology, 2024)
Global food security and environmental stability will be threatened by population growth, land usage, and land change. Proper soil management in plant production helps reduce temperature and humidity-induced plant deterioration. This study aims to identify soil physics health (SPH), microclimate characteristics, and the relationship between the two in managing organic and inorganic paddy fields. The research location is in Purwantoro District, Wonogiri Regency, using descriptive explorative research, with purposive soil sampling at work map, made by overlay thematic maps, resulting in 9 LMU. The observation and sampling were carried out in the maximum vegetative phase of plants, while the micro-climate is in the generation phase. The determination of the soil physics health status used the scoring method. Using the T-test, Pearson’s correlation test finds the relationship between SPH and micro-climate characteristics and the differences between the two. The results showed the distribution of SPH in organic farming is healthy (74.7) and very healthy (83.3), while inorganic farming is healthy (79.72). The temperature is optimal, ranging from 23.5°C to 30.1°C, but the humidity is minimum in the range of 35.3% to 76.1%. The SPH and micro-climate have a significant relationship, with a positive correlation between air and soil temperature with SPH and a negative correlation between air humidity and soil moisture.